A Qualidade da Interação Positiva e da Consistência Parental na sua Relação com Problemas de Comportamentos de Pré-Escolares - Bolsoni-Silva, Alessandra Turini [UNESP]; Marturano, Edna Maria (My University, 2007)
Studies have shown a relationship to exist between behavior problems in children and quality of parental practices such as communication, expressivity, consistency, and monitoring. This study aimed at describing relationships that parents have with their preschool children, and also at relating parenting skills to child behavior. We compared fathers' and mothers' social educational skills in two groups of children, with or without behavior problems at school. Research was conducted in a town in the State of Sao Paulo, BR. Participants were biological mothers and fathers of 48 preschoolers; twenty-five children presented behavior problems at school, and 24 had high social skills. Parents were individually interviewed at home. Results showed that fathers and mothers of socially skilled children were more consistent in their practices. They were more able to identify and describe their children's socially skilled behaviors. They also reported they gave more positive feedbak for their children's good behavior.
The quality of positive interaction and parental consistency as related to behavior problems in preschoolers
Keywords: Assessment of social behaviors; Behavior problems; Parental social educational skills